IMPROVING THE SYSTEM OF NATIONAL WRESTLING TECHNIQUES-TACTICS AND COMPETITION TRAINING (American Journal of Pedagogical and Educational Research, 2025)
This graduation work is devoted to the issues of in-depth study of the technical and tactical aspects of National Wrestling, their effective application in practice and improvement of the system of preparation of athletes for competitions. The work analyzes national methods of struggle, their technical and tactical approaches. In addition, physical, mental and technical training stages, training system and planning methods were considered in the preparation of athletes for competitions.